(untitled) (SAARC Journal of Agriculture, 2016)
Cultivating summer (monsoon season) tomatoes in Bangladesh holds promise as a profitable enterprise with which farmers can augment existing cropping patterns, since only small amounts of land are required. Using on-farm production data collected from 18farmers in Jessore District,gross margin and other economic indicators were estimated. Results indicate that, with careful management implemented early in the crop season, small farmers can earn impressive profits if they harvest summer tomatoes at least twice (two fruiting stages). With an average gross margin equivalent to US13,737 ha-1, for example, a smallholder that owns or leases only 0.028 ha (approximately 7 decimals) could earn more than US 350. In addition a very high rate of return over investment (5.66) was calculated for farmers harvesting four times during the seven month cultivation period. Nevertheless, additional research remains to fine-tune farmers management of the summer tomato crop in order increase profits further by lowering the costs associated with key inputs (e.g., more efficient hormone application), or by utilizing the inputs more effectivetly (e.g., timing the spraying of hormones to coincide fruitsetting with periods of high demand). Since summer grown tomatoes are also disease and pest risk prone, the development of effective integrated pest mangement strategies are also required in order to reduce the high level of chemical use observed. SAARC J. Agri., 13(2): 80-93 (2015)